Simulation of microplastic transport and dispersion based on a three-dimensional hydrodynamic particle-tracking model in the Beibu Gulf - Sun, Changhao; Guan, Yao; Hou, Wenhao; Wei, Huihua; Hu, Xiaowei; Jiang, Huichang; Su, Qiongyuan; Zhou, Xiong; Chen, Jie; Zhu, Zuhao (Frontiers in Toxicology, 2025)
The Beibu Gulf, a representative semi-enclosed bay in the South China Sea, experiences microplastic transport and dispersion governed by a complex interplay of monsoons, ocean circulation, and extreme weather events, warranting systematic investigation. We developed a numerical modeling framework by coupling a three-dimensional hydrodynamic model with a Lagrangian particle-tracking module, and validated it against in observations. The model quantitatively demonstrates high accuracy, with maximum spatial deviations below 6 km and relative standard deviations within 7%, confirming its suitability for simulating microplastic transport. The simulation results indicate that the transport of microplastics in the Beibu Gulf is primarily controlled by the oceanic hydrodynamic environment, while also being indirectly affected by the monsoon. During winter and autumn, the northeast monsoon dominates, whereas in spring and summer, the southwest monsoon prevails, with the overall circulation exhibiting a counterclockwise coastal current pattern. In spring, microplastics can disperse up to 205 km, while in summer, southwest monsoon conditions lead to the formation of nearshore high-concentration zones (∼20 μg/m3). Vertical transport significantly modulates plume structure, with summer pollution coverage expanding by over 70% compared to scenarios excluding vertical motion.Storm surge events further intensify hydrodynamic conditions. As a case study, Typhoon Yagi induced significant alterations in the hydrodynamic conditions of the Beibu Gulf: prior to the storm, tidal forces governed periodic flow variations; during and after the storm, intense circulations generated prominent counterclockwise vortices, with velocities reaching 2.8 m/s, substantially enhancing long-range microplastic transport and extending their spatial distribution. This study reveals the key characteristics of microplastic transport in the Beibu Gulf under varying seasonal and hydrodynamic conditions, providing a rigorous theoretical foundation for understanding regional microplastic dispersal patterns.